2006
DOI: 10.1038/nmat1613
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-controlled ferromagnetism in transparent oxide semiconductors

Abstract: The search for an ideal magnetic semiconductor with tunable ferromagnetic behaviour over a wide range of doping or by electrical gating is being actively pursued as a major step towards realizing spin electronics. A magnetic semiconductor having a high Curie temperature, capable of independently controlled carrier density and magnetic doping, is crucial for developing spin-based multifunctional devices. Cr-doped In(2)O(3) is such a unique system, where the electrical and magnetic behaviour-from ferromagnetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
262
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(279 citation statements)
references
References 23 publications
13
262
2
2
Order By: Relevance
“…[7][8][9][10][11] Commonly invoked host materials include ZnO, TiO 2 , In 2 O 3 and SnO 2 . Despite the progress in developing oxide DMSs, the underlying mechanism for ferromagnetic ordering is still under active debate.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Commonly invoked host materials include ZnO, TiO 2 , In 2 O 3 and SnO 2 . Despite the progress in developing oxide DMSs, the underlying mechanism for ferromagnetic ordering is still under active debate.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy to mention that Co/TiO 2 This results the decrement of conductivity. It is also observed that higher thickness Co/TiO 2 thin films show lower conductivity compare to the lower thickness one for both as-deposited and annealed.…”
Section: Resultsmentioning
confidence: 95%
“…Transparent magnetic oxides have a high potentiality for fabricating future multifunctional spintronic devices according to the various technological reports and roadmaps [1][2][3][4][5]. One of the approaches in achieving this goal is the doping of transition magnetic (TM) material into transparent oxide [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 To endow In 2 O 3 with better or special properties, they are often doped by transition metal (TM) ions in order to introduce ferromagnetisms to non-magnetic In 2 O 3 , which is called as diluted magnetic semiconductor (DMSs) and potentially applied in transparent spintronic devices. [7][8][9][10][11][12][13] For example, Farvid et al 14 prepared paramagnetic Cr doped C-In 2 O 3 nanocrystals while Singhal et al 15 synthesized ferromagnetic Fe doped C-In 2 O 3 nanoparticles. In addition, Philip et al 7 could control ferromagnetisms of Cr doped C-In 2 O 3 films by tuning carrier density.…”
Section: Introductionmentioning
confidence: 99%